Clinically mild encephalitis/encephalopathy with a reversible splenial lesion associated with Mycoplasma pneumoniae infection. Issue 1 (December 2016) - Yuan, Zhe-Feng; Shen, Jue; Mao, Shan-Shan; Yu, Yong-Lin; Xu, Lu; Jiang, Pei-Fang; Gao, Feng; Xia, Zhe-Zhi
Abstract Background Clinically mild encephalitis/encephalopathy with a reversible splenial lesion (MERS) is a clinico-radiological syndrome characterized by transient mild symptoms of encephalopathy and a reversible lesion in the splenium of the corpus callosum on magnetic resonance imaging (MRI). It is often triggered by infection. The common pathogens of MERS are viruses, especially influenza virus. However, Mycoplasma pneumoniae (M.pneumoniae ) are relatively rare pathogens for MERS. Case presentation Here we report two paediatric cases ofM.pneumoniae infection-induced MERS. The diagnosis ofM.pneumoniae infection was established based on polymerase chain reaction (PCR) and specific serum antibodies (IgM). Both of the two patients presented with mild encephalopathy manifestations and recovered completely within a few days. The initial MRI showed a lesion in the central portion of the splenium of the corpus callosum, which completely resolved on the seventh and eighth day after admission for case 1 and case 2. Lumbar puncture was performed in both patients, which revealed no pleocytosis. In case 1, the patient had hyponatremia, peripheral facial nerve paralysis, and rash. To the best of our knowledge, it is the first MERS case associated with peripheral nerve damage. In case 2, interleukin-6(IL-6) was moderately increased in the cerebrospinal fluid (CSF). It suggested that IL-6 may play a role in the pathogenesis ofM.pneumoniae -induced MERS. Conclusion Our study enriches the available information on the pathogens of MERS and provides valuable data for better understanding of this syndrome.